Minat Bekerja di Perusahaan Jepang di Indonesia pada Mahasiswa Sastra Jepang Semester Akhir di Perguruan Tinggi - Ratna Handayani; Elisa Carolina Marion; Natsumi Koda (Bina Nusantara University, 2013)
The term nenkoujoretsu as one characteristic of Japanese culture gives much influence on management system for Japanese companies operating in Indonesia, including promotion system for employee career development. This system is very much different from the promotion system of western companies. Current developments show promotion system in the company does not entirely focus on seniority and age, but focuses on educational background and individual achievement. Thus the implementation of nenkoujoretsu on Japanese companies has changed. Further research related to the implementation of nenkoujoretsu on Japanese companies in Indonesia was conducted by examining working interest in Japanese companies in Indonesia of the Japanese literature students at final semester. The scope of this study was students at final or seventh semester in STBA JIA-Bekasi, Universitas Al Azhar Indonesia-Jakarta, Universitas Darma Persada, STBA LIA-Jakarta, Universitas Bina Nusantara, and Universitas Nasional-Jakarta. This study used questionnaire and literature method. Purpose of this research is readers can understand about student interest in Japanese literature to work in Japanese companies in Indonesia. This study concludes most students of Japanese literature at final or seventh semester are interested in working in Japanese companies. A large part of the reasons for respondents who were interested in working in a foreign company is due to big salary. In addition, performance also plays an important role and determines the position and higher salary than the senior as well as the ability to apply skills in Japanese language and knowledge about Japanese.